Differential Rnai Responses of Nicotiana Benthamiana Individuals Transformed with a Hairpin-Inducing Construct During Plum Pox Virus Challenge - (:unkn) unknown (SPRINGER, 2014)
Gene silencing and large-scale small RNA analysis can be used to develop RNA interference (RNAi)-based resistance strategies for Plum pox virus (PPV), a high impact disease of Prunus spp. In this study, a pPPViRNA hairpin-inducing vector harboring two silencing motif-rich regions of the PPV coat protein (CP) gene was evaluated in transgenic Nicotiana benthamiana (NB) plants. Wild-type NB plants infected with a chimeric PPV virus (PPV:: GFP) exhibited affected leaves with mosaic chlorosis congruent to GFP fluorescence at 21 day post-inoculation; transgenic lines depicted a range of phenotypes from fully resistant to susceptible. ELISA values and GFP fluorescence intensities were used to select transgenic-resistant (TG-R) and transgenic-susceptible (TG-S) lines for further characterization of small interfering RNAs (siRNAs) by large-scale small RNA sequencing. In infected TG-S and untransformed (WT) plants, the observed siRNAs were nearly exclusively 21- and 22-nt siRNAs that targeted the whole PPV:: GFP genome; 24-nt siRNAs were absent in these individuals. Challenged TG-R plants accumulated a full set of 21- to 24-nt siRNAs that were primarily associated with the selected motif-rich regions, indicating that a trans-acting siRNAs process prevented viral multiplication. BLAST analysis identified 13 common siRNA clusters targeting the CP gene. 21-nt siRNA sequences were associated with the 22-nt siRNAs and the scarce 23- and 24-nt molecules in TG-S plants and with most of the observed 22-, 23-, and 24-nt siRNAs in TG-R individuals. These results validate the use of a multi-hot spot silencing vector against PPV and elucidate the molecules by which hairpin-inducing vectors initiate RNAi in vivo.